Obtención y caracterización de colorantes naturales a partir de la corteza y hojas de molle (Schinus molle) - Guamushig Chuquitarco, Sandy Elizabeth (2019)
The research was carried out in order to obtain and characterize natural dyes from the bark and leaves of molle (Schinus molle), the extraction process was carried out using Soxhlet simple distillation equipment, the dye was obtained through the application of 100% leaves and 100% bark dehydrated with a humidity of 5%, placing them inside the equipment and with the application of the solvents water 250 ml and alcohol 250 ml, later a filtration of the sample was done to separate solids and finally the evaporation of the solvents at a temperature of 40 ° C for 90 minutes so that it evaporates and only the dye is preserved. In the present investigation an experimental design was applied that allowed us to evaluate variables to differentiate the treatments with the solvents used in the extraction of the molle dye, by means of an Experimental Design A * B 2 ^ 2. The variables studied were the phytochemical characterization of the dye, the physical chemistry of total polyphenols and the level of absorbance present in each sample, thus identifying the best treatment between the polyphenol concentration and absorbance. With respect to the use of raw materials and solvents, we find that the combination between leaves and alcohol generates a greater absorbance capacity of the dye with an average of 1.07 ppm and to respect to the concentration of total polyphenols in the sample it is determined that the combination leaves and alcohol is the best with an average of 962.88 ppm, in the phytochemical analysis it was determined that the dye has an abundant amount of flavonoids and tannins, which help the coloration in textiles of positive results with regard to the coloring ability.